Assessment of Effectiveness of Work-Life Balance Systems in Opinions of Women and Men - Maria MAJEWSKA; Joanna NIEŻURAWSKA-ZAJĄC (Communications of International Proceedings, 2021)
The aim of the article was to present the results of research on the effectiveness of work-life balance (WLB) of employees in selected companies in Poland. The research group consisted of 1097 women and men working in Polish enterprises. The authors proposed a method for assessing the effectiveness of the incentive system from the perspective of employee satisfaction. The calculation procedure adopted in the work is one of the methods used to estimate various types of strategic gaps in the management of the organization and its environment, this time it was applied in order to obtain measures of the effectiveness of the motivational system. The results of the research suggest that the effectiveness of the company's work-life systems must be significantly improved. The biggest gap in the effectiveness of WLB's operation appeared in the case of child benefits and the possibility of choosing benefits by employees. The representatives of the Z generation of both genders are the most satisfied with the WLB programs offered to them.
Keywords: Work -Life Balance (WLB); Motivation; Women; Men; Effectiveness of Work - Life Balance Concept